DIFFERENTS PRUNE EFECT IN VINEGRAPES CV. VÊNUS PRODUCTION AND QUALIT - SOZIM, Marcello; AYUB, Ricardo Antonio; MALGARIM, Marcelo Barbosa (Scientia Agraria, 2007)
A trial was conduced in a commercial vineyard located in a south region of Parana State. The vinegrape cv. Vênus with twelve years old spaced by 2.5 x 1.5 m was used. The vinegrapes were submitted to mist and long pruned. The following variables were evaluated: percentage of sprouting; number of clusters; production; weigh medium of clusters, soluble solids (SS) and period of harvest. The percentage of buds pre-bloomed were different in mist prune and long prune treatments, the biggest medium was in mist prune (87,93%) when compared which long prune (76,68%). The weigh of clusters and the contents of soluble solids did not differ in both prunes. The production in plants submitted to long prune was twice as much as compared to mist prune, it was the double number of clusters when compared which the mist prune. The vinegrape ‘Vênus’ fructification prune in south area of Paraná State must be middle to long prune, with five or six buds per ramification, in other to obtain more clusters and show adequate vigor for the next winter prune. The prune influenced grapes ripening by delayed harvest for five days in long prune plants.